Double fatal consequences of distance metastasis in nasopharyngeal carcinoma after a completed chemoradiation in pregnancy: A case report - Utami, Niken A.; Muknisa, Liza (Narra Sains Indonesia, 2023)
Distant metastasis in nasopharyngeal carcinoma (NPC) patients is one of the reasons for the decreased life expectancy with the most common metastasis spreads are to the bone, liver, and lung. Hepatoma is the most frequent liver malignancy and is one of the highest causes of cancer death worldwide and this can be as a result of NPC metastasis. The aim of this case report was to present a patient with hepatoma in pregnancy as a result of NPC metastasis. A 34-year-old pregnant female at 24–25 weeks of gestation presented with a chief complaint of heartburn and unbearable pain radiating to the back. Previous medical history reported that the patient had a liver enlargement. The patient was G4P2A1 with a single living intrauterine fetus and active fetal movements. The patient has a history of NPC and received a completed chemoradiation one month prior to hospital admission. Physical examination showed bilateral rales and palpable diffuse multiple nodule masses in the upper right abdominal quadrant. Laboratory examination revealed anemia, thrombocytopenia, negative hepatitis B surface antigen (HBsAg), and elevated liver markers. Abdominal ultrasonography results showed multiple diffuse nodules in the liver. The patient was diagnosed with a metastatic hepatoma based on the clinical and imaging findings. During hospitalization, the patient repeatedly experienced pleural effusion with suspicion metastases. A few days later, the fetal movements stopped and the ultrasonography indicated negative fetal heart rate. After experiencing respiratory distress for hours, the patient expired the day after. This case highlights that due to the potential adverse effects of chemotherapy and radiotherapy, the initiation of these therapies should be carefully decided to avoid adverse effects to mother and fetus.